2022
DOI: 10.1038/s41592-022-01466-7
|View full text |Cite
|
Sign up to set email alerts
|

NeuroMechFly, a neuromechanical model of adult Drosophila melanogaster

Abstract: Animal behavior emerges from a seamless interaction between neural network dynamics, musculoskeletal properties, and the physical environment. Accessing and understanding the interplay between these intertwined elements requires the development of integrative and morphologically realistic neuromechanical simulations. Until now, there has been no such simulation framework for the widely studied model organism, Drosophila melanogaster. Here we present NeuroMech-Fly, a data-driven model of the adult female fly wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 90 publications
1
56
0
Order By: Relevance
“…Joint angles from all time points and flies were pooled to generate kernel density estimates. The angles are defined as described in Lobato-Rios et al, 2022 . …”
Section: Introductionmentioning
confidence: 99%
“…Joint angles from all time points and flies were pooled to generate kernel density estimates. The angles are defined as described in Lobato-Rios et al, 2022 . …”
Section: Introductionmentioning
confidence: 99%
“…A seventh, front-facing camera recorded spherical treadmill rotations that could be converted into fictive locomotor trajectories using FicTrac [34] (Figure 1m). Multi-view camera images (Figure 1n) were post-processed using DeepFly3D [33] to estimate 3D joint positions [40] (Figure 1o). These data were used to train a dilated temporal convolutional neural network (DTCN) [41] that could accurately classify epochs of walking, resting, head (eye and antennal) grooming, front leg rubbing, and posterior (hindleg and abdominal) movements (Figure 1p, Figure S1g).…”
Section: Recording Descending Neuron Population Activity In Tethered ...mentioning
confidence: 99%
“…Specifically, while analyzing head grooming DNs, we noticed a large pair of ventral neurons (Figure 5a) that sometimes exhibited asymmetric activity (Figure 5b, gray arrowheads) when flies appeared to touch one rather than both antennae (Video 5). To quantify this observation, we replayed limb 3D kinematics in NeuroMechFly, a biomechanical simulation of Drosophila [40] (Figure 5c). By detecting leg-antennal collisions as a proxy for antenna deflection, we found that occasional asymmetries (Figure 5d) did coincide with asymmetric activity in corresponding neural data (Figure 5b, purple traces).…”
Section: Identifying Individual Descending Neurons From Population Re...mentioning
confidence: 99%
See 2 more Smart Citations